Konten Religi Tanpa Verifikasi: Tantangan Literasi Hadits di Era Platform Digital dalam Perspektif Ulumul Hadis: Unverified Religious Content: Challenges of Hadith Literacy in the Era of Digital Platforms from the Perspective of Ulumul Hadith - Kana Afanin Ridha (Litera Academica Publishing, 2025)
Digital transformation has created a new paradigm in the dissemination and learning of hadith, bringing both revolutionary impacts and complex challenges for Muslims. This study comprehensively examines the anatomy of hadith content dissemination in the digital era and its implications for people's religious understanding. Through a qualitative approach with data analysis from various digital platforms (Instagram, YouTube, TikTok, and WhatsApp), the study reveals that: (1) 63% of hadith content on Instagram does not include the status of authenticity; (2) Hadith dissemination occurs through three main layers - religious influencers, online communities, and attractive visual designs; (3) Unverified hadith content has the potential to lead to doctrinal misunderstandings, community divisions, and deviant worship practices. The research findings show that while digital technology has democratized access to hadith knowledge, the speed of information dissemination is not matched by adequate verification mechanisms. The characteristics of social media that encourage virality and high engagement have the potential to exacerbate the spread of false (maudhu') and weak (dha'if) hadith. On the other hand, the study also identified transformative opportunities through hadith verification applications, online courses, and creative educational content. The implications of this study emphasize the importance of multidisciplinary collaboration between scholars, academics, technology developers, and communities to build a healthy digital ecosystem. Policy recommendations include: strengthening digital hadith literacy, developing AI-based verification tools, and drafting religious content guidelines for digital platforms. This research makes a significant contribution to the development of contemporary hadith studies and proselytization practices in the digital era.